Effectiveness of Cooperative Learning For Improving Learners’ Proficiency Level of English Language in Secondary Level Education in Nepal (Journal of NELTA, 2018)
This longitudinal research study aims at investigating the effectiveness of cooperative learning (CL) for improving learners’ English language proficiency (ELP) level in secondary level education in Nepal. The study comprises 150 learners from grade 10 in the academic session of 2017 among whom 78 learners were chosen for experimental group while 72 for control group. The instruments of proficiency test, questionnaire and interview were used to obtain data that were analyzed using mean, standard deviation, Mann-Whitney Utest and bar graphs. The result shows the effectiveness of CL for improving learners’ ELP level that the overall performance of experimental group of students (M = 26.71, SD = 4.478) in English language was found far better than that of control group of students (M = 16.50, SD = 5.619) with significant difference (p < 0.001).Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, Page: 13-25